Efektivitas Media Pembelajaran Matematika Berbasis Android Untuk Meningkatkan Minat Belajar Siswa Sekolah Dasar - Abdul Rohman (Papanda Journal of Mathematics and Science Research, 2023)
The increasing use of smartphones among elementary school students is a concern because students are lazy to increase their interest in learning. This study aims to analyze the effectiveness of Android-based learning media to increase students' interest in learning in elementary schools. The design in this study used a Quasi-Experimental Design experimental research method. The results of the analysis of the effectiveness test, the normality test showed the value of Sig. the experimental group was 0.094 and the control group was 0.101. Because the value of the two groups is> 0.05, it can be concluded that the learning outcome data is normally distributed. While the homogeneity test, it is known that the significance value (Sig.) Of learning outcomes is 0.215 because 0.215> 0.05, it is concluded that the data variant of mathematics learning outcomes is homogeneous. The t-value calculation is 2.442 while the t-table value is 2.032. If the value of t-count> t-table, then Ho is rejected and Ha is accepted with the assumption that there are significant differences in learning outcomes with different learning media. The n-Gain value of 0.467 in Hake's N-Gain criteria table is in the medium category. So the conclusions that can be taken in Android-based mathematics learning media are effective in increasing student interest in learning